Effects of Paclitaxel and combination of the drug with radiation therapy in an in vivo model of anaplastic thyroid carcinoma - Pushkarev, V.M.; Starenki, D.V.; Saenko, V.O.; Tronko, M.D.; Yamashita, S. (Experimental Oncology, 2011)
Aim of this article is to study the effects of Paclitaxel (Ptx), γ-irradiation (IR) and their combination on the growth of xenografted tumors derived from undifferentiated thyroid cancer cells.